Penerapan Wordwall Sebagai Media Evaluasi Pembelajaran pada Mata Pelajaran Sistem dan Instalasi Refrigerasi - Eriko, Yus; Yanto, Doni Tri Putra (Jurnal Pendidikan Teknik Elektro, 2024)
Currently, it cannot be denied that the implementation of evaluation in learning must adapt to digital and leave manual systems slowly because many digital products have been developed to make it easier for teachers and students to measure students' abilities in understanding learning. In the 21st century, life is made easier with various types of digital that are continuously developing to be used in life, including in learning. Digital products that are web-based and use an internet connection are a necessity in this century. One learning evaluation media that can be applied is using the Wordwall application. Wordwall is a piece of software that works online and is used as a game-based learning medium for kahoots, quizzes, and so on. This research aims to determine how the implementation and effectiveness of the application of Wordwall in the Refrigeration Systems and Installation subject is seen from the learning outcomes of the class pretest-posttest group. The research process begins with the pretest stage, which aims to assess students' initial understanding of the material they have studied. After the pretest, students are given treatment by applying Wordwall as a learning evaluation medium after which a posttest is carried out. This posttest aims to evaluate students' understanding after taking part in the evaluation with the Wordwall application. The pretest and posttest results will be analyzed using effect size and student learning completeness. Based on the research results, it show that there are differences in students' scores before and after implementing Wordwall as a learning evaluation medium. The results of classical completeness testing and effect size show that implementing wordwall effectively improves student learning outcomes.